Porcine Circovirus Type 3 Enters Into PK15 Cells Through Clathrin- and Dynamin-2-Mediated Endocytosis in a Rab5/Rab7 and pH-Dependent Fashion - Shi, Ruihan; Hou, Lei; Wei, Li; Quan, Rong; Zhou, Bin; Jiang, Haijun; Wang, Jing; Zhu, Shanshan; Song, Jiangwei; Wang, Dan; Liu, Jue (Frontiers in Microbiology, 2021)
Porcine circovirus type 3 (PCV3) invades multiple tissues and organs of pigs of different ages and are widely spread throughout pig farms, emerging as an important viral pathogen that can potentially damage the pig industry worldwide. Since PCV3 is a newly discovered virus, many aspects of its life cycle remain unknown. Porcine kidney epithelial cells are important host targets for PCV3. Here, we used systematic approaches to dissect the molecular mechanisms underlying the cell entry and intracellular trafficking of PCV3 in PK15 cells, a cell line of porcine kidney epithelial origin. A large number of PCV3 viral particles were found to colocalize with clathrin but not caveolin-1 after entry, and PCV3 infection was significantly decreased when treated with chlorpromazine, dynasore, knockdown of clathrin heavy chain expression via RNA interference, or overexpression of a dominant-negative mutant of EPS15 in PCV3-infected cells. After internalization, the viral particles were further observed to colocalize with Rab5 and Rab7, and knockdown of both expression by RNA interference significantly inhibited PCV3 replication. We also found that PCV3 infection was impeded by ammonium chloride treatment, which indicated the requirement of an acidic environment for viral entry. Taken together, our findings demonstrate that PCV3 enters PK15 cells through a clathrin- and dynamin-2-mediated endocytic pathway, which requires early and late endosomal trafficking, as well as an acidic environment, providing an insightful theoretical basis for further understanding the PCV3 life cycle and its pathogenesis.